(untitled) (Fiep Bulletin - online, 2013)
This paper is a case study of a 47-year-old female patient with hemorrhagic vascular accident – left hemiparesis, carried out over a period of 20 months with sessions performed daily. The purpose of this experiment is to achieve the proper family and social integration by reaching functional independence. In the recovery strategy used, the focus was on the use of the proprioceptive and neuromuscular facilitation techniques in order to improve postural control and motor ability, by using different combinations of these techniques during each stage of the motor control. The results achieved support the statement according to which remarkable results can be achieved only through a cooperation of the interdisciplinary team in which the patient, his/her family and the physical therapist have the main role.